Fontes energéticas alternativas na alimentação de cabras Saanen em lactação - Hygino, Bruna (2015)
The objective in this study was to characterize and evaluate the nutritional values and nutritive of feeds used in diets for Saanen goats, and its effects on milk production and blood parameters. Five Saanen goats after 60 days in milk (56.7 ± 5.22 kg and average daily production of 3.0 L of milk) were distributed in 5x5 latin square design and fed diets composed of Tifton 85 hay and concentrate rations containing soybean meal, mineral-vitamin supplement, common salt and different energy sources: ground corn, soybean hulls, ground ear corn, cassava byproduct and corn + protected fat. Contents were determined for dry matter, ash, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, physically effective fiber and lignin. Organic matter, total carbohydrates and non-fiber carbohydrates were estimated. Carbohydrates were divided into fractions A + B1 (rapidly degradable carbohydrates), fraction B2 (potentially degradable carbohydrates) and fraction C (non-degradable carbohydrates); and the protein in the fractions A (soluble), fraction B1 (rapid ruminal degradation), B2 fraction (intermediate degradation), B3 fraction (slow degradation) and fraction C (indigestible). To determine the total gas production and kinetics of ruminal fermentation parameters, the automatic technique in vitro was used, modified by Ankom®. The dry matter intake was estimated by the difference between the supplied food and the orts in the days of sampling. Indigestible acid detergent fiber was used as internal marker to estimate the digestibility of dry matter and nutrients. The control of milk production was done by weighing it every milking. Goats' blood samples were collected to analyze the concentrations of glucose, triglycerides, cholesterol and urea. Simplified economic analysis was performed to determine the benefit:cost of feed used. Differences were observed (P <0.05) among the parameters A, B, C, E and A + D of ruminal degradation kinetics. Significant differences were observed in the ether extract intakes and total digestible nutrients. Treatments that showed better results for digestibility were soybean hulls and cassava byproduct. Milk production, production corrected for 35 g fat/kg of milk and production efficiency did not differ among different energy sources. The highest blood urea levels were observed for treatments containing cassava byproduct and corn + protected fat. The treatment containing ground ear corn presented the best cost: benefit ratio. The total gas production was higher in feeds with a high content of non-fiber carbohydrates, namely: ground corn, ground ear corn and cassava byproduct, result of a higher fraction A, with rapid degradation, observed for these feed. The inclusion of alternative energy sources in diets for lactating goats Saanen does not alter the dry matter intake, milk production and production efficiency. As for digestibility, the best results can be attributed to treatments containing soybean hulls and cassava byproduct, however, the treatment containing ground ear corn showed the best cost: benefit ratio.